La Neuropublicidad en la industria comercializadora de gorras y sombreros en Tungurahua - Martínez Núñez, Pablo Andrés (2024)
Neuro publicity, by understanding sensory and neural studies, directs all its analysis and experimentation towards the senses, seeking as a response the brain behavior of a group of people to advertising stimuli. Due to this, companies and brands use various techniques, such as a color palette based on consumer preferences or an aroma that identifies a product and that, upon perceiving it, is immediately recognized. The objective of this research is to determine the influence of Neuro publicity and its relevance in the potential growth of an emerging brand of caps and hats from Ambato, a city that is a productive engine of the Tungurahua province and the country. Can its application increase sales probabilities, customer loyalty, or recognition? This study aims to gather all possible information to develop a Neuro publicity application model for small and medium textile businesses and analyze the effectiveness of each technique that has turned this discipline into a true persuasion weapon.